Estimation of lifetime costs for patients receiving a transplant: the case of liver transplantation related to hepatitis B in Italy - Marzano, Alfredo; Canali, Beatrice; De Carlis, Luciano; De Simone, Paolo; Fiorentino, Francesca; Rendina, Maria; Vassallo, Chiara; Fagiuoli, Stefano (Frontiers in Public Health, 2024)
In Italy, post-liver transplant (LT) hepatitis B virus (HBV) reinfection prophylaxis is frequently based on a combined regimen of anti-HBV immunoglobulin (HBIG) and oral antivirals. However, little information is available at the national level on the cost of LT and the contribution of HBV prophylaxis. This study aimed to quantify the direct healthcare cost for adult patients undergoing LT for HBV-related disease over a lifetime horizon and from the perspective of a National Healthcare Service.A pharmaco-economic model was implemented with a 4-tiered approach consisting of 1) preliminary literature research to define the research question; 2) pragmatic literature review to retrieve existing information and inform the model; 3) microsimulated patient cycles; and 4) validation from a panel of national experts.The average lifetime healthcare cost of LT for HBV-related disease was €395,986.The greatest cost drivers were post-transplant end-stage renal failure (31.9% of the total), immunosuppression (20.6%), and acute transplant phase (15.8%). HBV reinfection prophylaxis with HBIG and antivirals accounted for 12.4% and 6.4% of the total cost, respectively; however, lifetime HBIG prophylaxis was only associated with a 6.6% increase (~€422 k). Various sensitivity analyses have shown that discount rates have the greatest impact on total costs.